Synthesis and preliminary evaluation of the anti-cancer activity on A549 lung cancer cells of a series of unsaturated disulfides. Issue 1 (20th December 2018) - Olivito, Fabrizio; Amodio, Nicola; Di Gioia, Maria Luisa; Nardi, Monica; Oliverio, Manuela; Juli, Giada; Tassone, Pierfrancesco; Procopio, Antonio
Abstract : In this work we synthesized and tested a series of unsaturated disulfides. Two compounds showed a promising anticancer activity in vitro on A549 lung cancer cells compared to the natural analogue. Abstract : We synthesized a series of small symmetrical unsaturated disulfides by a multi-step reaction starting from organic alcohols, and we performed a preliminary test to evaluate the effect of these compounds on the viability of A549 lung cancer cells. The garlic-derived natural compound diallyl disulfide, known for its anticancer activity, was used as the lead compound in this study. We synthesized five DADS analogues having different carbon chain lengths and different positions of the double bonds. Two analogues exhibited a promising antitumor activity in vitro, and the allylic double bond did not seem to be the main driving force.